The Cellular Prion Protein—ROCK Connection: Contribution to Neuronal Homeostasis and Neurodegenerative Diseases - Schneider, Benoit; Baudry, Anne; Pietri, Mathéa; Alleaume-Butaux, Aurélie; Bizingre, Chloé; Nioche, Pierre; Kellermann, Odile; Launay, Jean-Marie (Frontiers in Cellular Neuroscience, 2021)
Amyloid-based neurodegenerative diseases such as prion, Alzheimer’s, and Parkinson’s diseases have distinct etiologies and clinical manifestations, but they share common pathological events. These diseases are caused by abnormally folded proteins (pathogenic prions PrPSc in prion diseases, β-amyloids/Aβ and Tau in Alzheimer’s disease, α-synuclein in Parkinson’s disease) that display β-sheet-enriched structures, propagate and accumulate in the nervous central system, and trigger neuronal death. In prion diseases, PrPSc-induced corruption of the physiological functions exerted by normal cellular prion protein (PrPC) present at the cell surface of neurons is at the root of neuronal death. For one decade, PrPC emerges as a common cell surface receptor for other amyloids such as Aβ and α-synuclein, which relays, at least in part, their toxicity. In lipid-rafts of the plasma membrane, PrPC exerts a signaling function and controls a set of effectors involved in neuronal homeostasis, among which are the RhoA-associated coiled-coil containing kinases (ROCKs). Here we review (i) how PrPC controls ROCKs, (ii) how the PrPC-ROCK coupling contributes to neuronal homeostasis, and (iii) how the deregulation of the PrPC-ROCK connection in amyloid-based neurodegenerative diseases triggers a loss of neuronal polarity, affects neurotransmitter-associated functions, contributes to the endoplasmic reticulum stress cascade, renders diseased neurons highly sensitive to neuroinflammation, and amplifies the production of neurotoxic amyloids.